1972
DOI: 10.1111/j.1432-1033.1972.tb01745.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pathway of Glutamate Oxidation in Rabbit Reticulocytes

Abstract: I.It is shown by means of experiments on intact cells with 14C-labelled substrates that the first step in the oxidative metabolism of glutamate in rabbit-reticulocytes is a transamination with oxaloacetate to form aspartate. 2.The aspartate is metabolized further in such a manner that CO, is formed from all C-atoms. With tracer amounts of glutamate no accumulation of aspartate occurs, in contrast to isolated mitochondria. The mechanism of the utilization of aspartate appears to be a decarboxylation of oxaloace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1972
1972
1982
1982

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Oxaloacetate itself is a good substrate of both intact reticulocytes [14] and their isolated mitochondria [15]. From experiments with [U-14C]glutamine as predominant respiratory substrate it has been postulated [4] that the carbon skeleton of glutamate furnishes acetyl-CoA via oxaloacetate and pyruvate. Thus oxaloacetate and amino acids which form it are sources of acetyl-CoA competitive with the fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…Oxaloacetate itself is a good substrate of both intact reticulocytes [14] and their isolated mitochondria [15]. From experiments with [U-14C]glutamine as predominant respiratory substrate it has been postulated [4] that the carbon skeleton of glutamate furnishes acetyl-CoA via oxaloacetate and pyruvate. Thus oxaloacetate and amino acids which form it are sources of acetyl-CoA competitive with the fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous communication it was concluded that in reticulocytes oxaloacetate which arises from amino acids, in particular glutamate and aspartate, may also be the source of pyruvate and acetyl-CoA [1 ]. The evidence was indirect; it consisted in dilution experiments, which showed a diminution of 14 CO2 formation from variously labelled 14 C pyruvate from ~4C acetate, as well as 14 C-labelled fatty acids by glutamine and oxaloacetate.…”
Section: Introductionmentioning
confidence: 99%
“…The third pool consists of the components of the citrate cycle, in particular citrate, and of the amino acids which are closely related to the citrate cycle, such as glutamate and aspartate [38].…”
Section: Meiaholic Pathwaysmentioning
confidence: 99%